2023
DOI: 10.1002/advs.202301492
|View full text |Cite
|
Sign up to set email alerts
|

CD8 T Cell‐Derived Exosomal miR‐186‐5p Elicits Renal Inflammation via Activating Tubular TLR7/8 Signal Axis

Abstract: T cells play an important role in the development of focal segmental glomerulosclerosis (FSGS). The mechanism underlying such T cell‐based kidney disease, however, remains elusive. Here the authors report that activated CD8 T cells elicit renal inflammation and tissue injury via releasing miR‐186‐5p‐enriched exosomes. Continuing the cohort study identifying the correlation of plasma level of miR‐186‐5p with proteinuria in FSGS patients, it is demonstrated that circulating miR‐186‐5p is mainly derived from acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…Secondly, serum exosomal miR-186-5p was positively correlated with Scr and inversely linked with eGFR in AMI patients receiving PCI. It would be due to the fact that exosomal miR-186-5p might modulate Smad5 and toll-like receptor 7/8 axis to induce renal inflammation and fibrosis, which impaired renal function and resulted in a higher Scr and lower eGFR ( 24 , 25 ). Thirdly, serum exosomal miR-186-5p was positively related to CRP in AMI patients receiving PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, serum exosomal miR-186-5p was positively correlated with Scr and inversely linked with eGFR in AMI patients receiving PCI. It would be due to the fact that exosomal miR-186-5p might modulate Smad5 and toll-like receptor 7/8 axis to induce renal inflammation and fibrosis, which impaired renal function and resulted in a higher Scr and lower eGFR ( 24 , 25 ). Thirdly, serum exosomal miR-186-5p was positively related to CRP in AMI patients receiving PCI.…”
Section: Discussionmentioning
confidence: 99%
“…found that miR-186–5p in CD8 T cell-derived exosomes caused renal inflammation and tissue damage. miR-186–5p directly activates TLR7/8 signaling axis in renal tubules to cause renal inflammation, which reveals the specific pathogenic mechanism and reason of the pathogenic role in T cell-mediated renal dysfunction and provides new ideas for the treatment of nephropathy ( 311 ). T cell-derived exosomes are still in the exploratory stage, and continuous efforts are still needed to achieve clinical transformation.…”
Section: Immune Cell-derived Exosomes (Im-exo) In Cancer Therapymentioning
confidence: 99%